Hepatitis E Infection in HIV-Infected Patients - Rivero-Juarez, Antonio; Lopez-Lopez, Pedro; Frias, Mario; Rivero, Antonio (Frontiers in Microbiology, 2019)
Background The hepatitis E virus (HEV) represents a major cause of acute hepatitis worldwide. The majority of HEV cases occur in low-income countries, mainly Asia and Africa, where HEV causes large outbreaks associated with the consumption of contaminated water and high mortality in specific populations. In high-income countries, HEV infection is considered a zoonotic disease that is linked to the consumption of contaminated food. Although a high proportion of cases have self-limiting asymptomatic or subclinical infections, immunosuppression may modify the pathogenesis and clinical impact of this emerging disease. Results and Discussion Here, we review the current knowledge about the epidemiology, diagnosis, clinical manifestations, management and prevention of HEV infection in HIV-infected subjects. Conclusions Despite the increasing knowledge about the pathogenesis, epidemiology and clinical impact of HEV infection, several major factors are faced by HIV-infected patients, including treatment recommendations, immunization and risk practices.